Effect of oral pilocarpine on post-irradiation xerostomia in head and neck cancer patients: A single-center, single-blind clinical trial - Chitapanarux I. (2014)
Objective: The authors determined the efficacy and safety of oral pilocarpine tablet in symptomatic relief of post-radiation xerostomia in head and neck cancer patients. Material and Method: Thirty-three radiation-induced xerostomia patients were enrolled in a single-blind method to receive placebo 1-tablet three times daily in the first month and then oral pilocarpine (5 mg) 1-tablet three times daily for the next three months. Patients were evaluated for subjective symptomatic relief of xerostomia using questionnaires. Objective findings of xerostomia were also evaluated at the same time by two radiation oncologists. Results: All 33 patients had received radiotherapy doses at least 4000 cGy to the parotid glands. Improvement of xerostomia symptoms was observed, with a mean total subjective xerostomia score improvement at the first 4 weeks of oral pilocarpine treatment (p = 0.001), and later throughout the present study. Objective xerostomia score also showed statistically significant improvement at the same time point. Adverse effects of pilocarpine included sweating, nausea, palpitation, and tearing, with sweating as the most common side effect. Adverse effects of placebo included mild headache, nausea, and vomiting. Conclusion: Oral pilocarpine was effective and well tolerated in the treatment of radiation-induced xerostomia symptoms.